The Role of Mathematics Goes to School in Efforts to Improve Numeracy Literacy of Grade X Students at MA Muhammadiyah 2 Yanggong - Ananda Eriana; Wahyudi Wahyudi; Dwi Avita Nurhidayah (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2026)
The level of numeracy literacy among Indonesian students is relatively low, as shown in PISA 2023, which makes it difficult for students to connect mathematical concepts to everyday life. This is also evident at MA Muhammadiyah 2 Yanggong, where students are often trapped in memorizing unclear formulas without understanding the meaning of the problems they encounter. This study aims to explain the implementation of the Mathematic Goes to School (MGTS) program, a work program of HMPS Pendidikan "Delta", as an effort to improve students' numeracy literacy through contextual learning. This study applies a qualitative approach with an intrinsic case study. Participants in this study were grade X students of MA Muhammadiyah 2 Yanggong, in the 2024/2024 academic year. Data were collected through direct observation, student reflections, and documentation, which were then analyzed using the Miles and Huberman model, comprising data reduction, data presentation, and conclusion drawing. The results show that the MGTS program successfully changed the way students learn, from simply calculating to analyzing and solving problems. Despite the limited timeframe, this program has proven effective in transforming students' learning attitudes, making them more critical and active. The collaboration between students as peer mentors and the school, using a realistic approach, has had a positive impact on strengthening students' numeracy literacy at the secondary level.